Psychoactive Synthetic Adulterants in Tablets Sold as MDMA after the COVID-19 Pandemic: Implications for Central Effects - De Luca, Maria Antonietta; Miliano, Cristina; Roxburgh, Amanda; Graham, Myfanwy; Caria, Francesca; Guirguis, Amira; Schifano, Fabrizio; Nielsen, Suzanne; Simola, Nicola; Costa, Giulia (Current Neuropharmacology, 2026)
<span class=
Keywords: Amphetamines